Novel approaches for colorimetric measurements in analytical chemistry – A review - Fernandes, Gabriel Martins; Silva, Weida R.; Barreto, Diandra Nunes; Lamarca, Rafaela S. [UNESP]; Lima Gomes, Paulo Clairmont F. [UNESP]; Flávio da S Petruci, João; Batista, Alex D. (Elsevier, 2020)
Colorimetric techniques have been developed and used in routine analyses for over a century and apparently all their potentialities have been exhaustively explored. However, colorimetric techniques have gained high visibility in the last two decades mainly because of the development of the miniaturization concept, for example, paper-based analytical devices that mostly employ colorimetric reactions, and by the advances and popularity of image capture instruments. The impressive increase in the use of these devices was followed by the development and enhancement of different modes of color detection to meet the demands of making qualitative, semi-quantitative, and fully quantitative analyses of multiple analytes. Cameras, scanners, and smartphones are now being used for this purpose and have become suitable alternatives for different approaches to colorimetric analysis; this, in addition to advancements in miniaturized devices. On the other hand, recent developments in optoelectronics technologies have launched more powerful, more stable and cheaper light-emitting diodes (LEDs), which once again have become an interesting tool for the design of portable and miniaturized devices based on colored reactions. Here, we present a critical review of recent developments and challenges of colorimetric detection in modern analytical chemistry in the last five years, and present thoughts and insights towards future perspectives in the area to improve the use of colorimetric detection in different application approaches.
Keywords: Colorimetric detection; Colorimetry; Computer vision-based detection; Digital images